Fine-scale habitat use by black-footed ferrets (Mustela nigripes) released on black-tailed prairie dog (Cynomys ludovicianus) colonies in New Mexico - Chipault, Jennifer G., author; Detling, James K., advisor; Biggins, Dean E., advisor; Reich, Robin M., committee member (Colorado State University. Libraries, 2010)
Black-footed ferrets (Mustela nigripes) are among the most endangered animals in North America. The dependency of ferrets on diminishing prairie dog {Cynomys spp.) colonies for prey and shelter has been detrimental to their persistence in the wild. Reintroductions of captive-born ferrets into remaining prairie dog complexes have become crucial to the conservation of the species. Gaps in knowledge of ferret behavior hinder the success of these reintroductions. In this study, fine-scale prairie dog burrow density use by captive-born ferret kits was analyzed to inform future management. In September 2007, captive-born ferrets were released on a black-tailed prairie dog (C. ludovicianus) colony on the Vermejo Park Ranch in northern New Mexico. Locations {n = 46) from 16 ferret kits experimentally released in areas of comparatively low and high prairie dog burrow densities were obtained via spotlight surveys. Ten kits were subsequently translocated to low and high burrow density areas on other Vermejo colonies and located thereafter (« = 53). For two months, habitat use was quantified by mapping all burrow openings within a 30 m radius of where ferrets were located. Spatial autoregressive models and spatially-explicit t-tests were used to account for autocorrelation in the used burrow densities. It was hypothesized that ferrets released in, or translocated to, areas of low burrow densities would move so as to increase their localized burrow densities as they spent more nights in the wild. It was also hypothesized that ferrets released in, or translocated to, high burrow density areas would maintain high used burrow densities. There was an inverse relationship between used prairie dog burrow densities and nights in the wild for ferrets released in high burrow density areas. For ferrets translocated to high burrow density areas, a pattern was not detected in burrow densities over time, which does not contradict the hypothesis for these ferrets. However, burrow densities used by ferrets released in, and translocated to, low burrow density areas did not increase over time as expected. With the number of nights in the wild converted to release or translocation burrow densities versus ferret-used burrow densities, average used burrow densities increased for ferrets placed in low burrow density areas, and average used densities decreased for ferrets placed in high burrow density areas. Used burrow densities on most inhabited colonies were similar to available densities, except for one colony, where used densities were lower than available densities. Because newly-released ferrets in this study used burrow densities similar to densities available at the colony level, releasing ferrets on colonies offering overall high burrow densities might increase reintroduction success rates. Furthermore, burrow densities directly correlated with prey densities in this study. Ferrets used higher burrow densities before midnight; future research on ferret habitat use should consider within night variation. Other studies on ferret habitat use after release are necessary; kits monitored for more than two months, or with experience in the wild at a younger age, might select high burrow density areas within colonies as predicted.
Covers not scanned.
Keywords: Black-footed ferret -- Habitat; Black-tailed prairie dog -- Habitat